“Equivalence of living conditions” and impact forces of spatial structuring: On the treatment of a programme in times of globalisation - Brake, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
Systematic changes in spatial structuring are eroding the habitual relationship between the place-based economy and low mobility. Sparsely settled areas with a new quality in the enlarged area of the Federal Republic of Germany and patterns of depopulation in the course of demographic change as well as an affinity to the urbanity of the knowledge economy are reinforcing unequal spatial development. This puts the traditional treatment of areas with low dynamics or sparse settlement massively into question and calls for a re-examination of expectations of justice. A re-interpretation of “equivalent living conditions” must allow a treatment of more strongly differentiated conditions, which promises sustainable functioning spatial structures. The promise of appropriate working and living conditions for everyone where he is growing up must be substituted by his enablement to lead a life in keeping with the times, possibly elsewhere (equality of chances). For a participation in working life adapted activities must also promoted in areas with low dynamics or sparse settlement. Instead of redistribution a self-responsible enablement is more strongly emphasised, but not as a relinquishment of common development and responsibility. Challenges and tasks (basic conditions/approaches) aim at an “infrastructure of enablement”, as far as feasible spatial roles, comprehensive communication, orientation (education) and co-operation are concerned. The article advocates a reality-oriented and insofar future-oriented treatment of unequal living conditions instead of normative invocations. In view of a fundamentally more strongly segregating spatial structure, the tendentially uninhabited areas should remain less a taboo than be an incitement for new differentiation-, co-operation- or cohesion concepts, in order to meet also the fiction of “catching up in development” or factual “passive redevelopment”.